ANALISIS PENERAPAN KEADILAN SOSIAL DALAM AKSES DAN PELAYANAN KAMPUS UNIVERSITAS JEMBER - Sihaloho, Alga Alwesker; Ratna Endang Widuatie; Aurellia Rahmadhina; Setya Nikita Aprilia ArumingTyas; Silva Izza Afcarina; Syava Zulfania Zahra (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyze the perceptions of Jember University students regarding the implementation of social justice values on campus, including aspects of equality in academic guidance, campus facilities, and attention and support from the campus. The research method used a quantitative descriptive approach with data collection through a Likert-scale questionnaire completed by students from various faculties using a simple random sampling technique. The results showed that the majority of students assessed the implementation of social justice values as running well, with an average score of positive perception (4.1 out of 5). These findings indicate that the university has strived to implement the principle of equality without discrimination, provide adequate access to facilities, and support solidarity among students. However, several challenges such as limited disability-friendly facilities and inequality in social participation still require attention. The implementation of social justice values is strengthened by students' social awareness and an inclusive campus culture. This study provides recommendations for increasing inclusivity and strengthening social justice values through sustainable policies and programs as an actualization of Pancasila values in the higher education environment.